Nanosized Particles of Silica and Its Derivatives for Applications in Various Branches of Food and Nutrition Sectors - Mohammad Reza Kasaai (Journal of Nanotechnology)
Nanosized particles of silica and its derivatives have been identified as versatile for a broad range of science, technology, and engineering applications. In this paper, an effort has been made to provide a short review from the available literature information on their applications in various branches of food and nutrition sectors. The information provided in this paper describes various parameters affecting their performances and efficiencies. The properties and applications of nanosilica and its derivatives have been compared with microsilica and bulk-silica for their performances. The use of nanosized particles of silica and its derivatives provides a number of advantages. Their efficiencies and performances are significantly higher than those of the traditional ones.